La petite société à l’image de la grande ? L’appartenance fondée dans le mérite ou le droit - Maroussia Raveaud (Recherches en Éducation)
Kindergarten classrooms offer an initial contact with knowledge to 5-year-old children by organizing an interaction with the world that is not only lived, but also studied. The child’s active participation in the proposed situations represents a developmental opportunity (Rogoff, 1990; Rogoff & al., 2005; St. Clair, 2008). However, the new student must not only understand the teacher’s intention to transmit knowledge in these activities, but also the new role that must be fulfilled, including its social, intellectual and affective components. The specificity of kindergarten centralizes the question of shared signification in the joint activity of the teacher and his students (Grossen, 2014; Moro, Muller Mirza & Roman, 2014). This article looks at rituals as prototypes of theses joint activities, all while defining psychological and didactic conditions associated to the integration of the child into the school posture, characterized not only by new social forms, but also by new forms of thinking (Moro & Rodriguez, 2014).